Effects of three different stunning/slaughtering methods on physical, chemical, and sensory changes in rainbow trout (Oncorhynchus mykiss). (13th August 2018) - Concollato, Anna; Dalle Zotte, Antonella; Vargas, Sheyla C; Cullere, Marco; Secci, Giulia; Parisi, Giuliana
Abstract: BACKGROUND: Electrical stunning (E) and asphyxia in the air (A) are two common stunning/killing methods for fish. However, they can stress the fish and affect flesh quality, so an alternative should be found. The present study aimed to evaluate the effects of carbon monoxide asphyxia (CO) compared to E and A on the evolution of post rigor mortis changes in rainbow trout ( Oncorhynchus mykiss ) fillets related to chemical, textural, and sensorial properties during storage time. RESULTS: Fish fillets from the E group showed a higher pH ( P < 0.05) than the A ones, both at time of rigor resolution (TRR 0) and from TRR 4 until TRR 7 (7 days after rigor resolution, which corresponded to 10 days post mortem ), with the CO group being always intermediate. The CO treatment ensured that the fillets showed the lowest yellowness index (b*), even if only at TRR 2 and TRR 5. Lipid oxidation and texture profile analyses were unaffected. Sensory analysis revealed that the CO fillets had the lowest odor intensity and the highest juiciness scores ( P < 0.05). The sensory descriptors resulted the most discriminant variables of the fillets obtained from the differently stunned animals, as resulted by the canonical discriminant analysis. CONCLUSION: The carbon monoxide stunning/slaughtering method could be applied to rainbow trout without detrimental effects on physical, chemical, or sensory characteristics of the fish flesh. © 2018 Society of Chemical Industry